Sensitivitas Jender dalam Security Sektor Reform (SSR) - Fauziah, Nurul (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2019)
Sensitive gender is often discussed in the security issues in various academic literature and official documents. Many literatures are claiming that sensitive gender has succeeded in resolving cases of women violence, especially sexual violence against women in conflict countries. However, not many experts gave different opinions. By using the literature review method through the collection of the latest journals and literature, this study attempt to map the gender sensitivity debate in Security Sector Reform (SSR) to look back on the urgency of gender-sensitive SSR practices in a region. Based on the results of the analysis, gender sensitivity in the SSR as a transformation of the Internal structure of security sector institutions that fullness women’s equality in full, women’s participation and representation in security, supervision and management sector institutions are still controversial. However, according to the author, the presence and role of women in gender sensitivity in SSR can also contribute to influencing the design and implementation of peace missions through their role in describing the experiences of women as victims of conflict or war.